2002
DOI: 10.1161/01.cir.0000017361.39256.82
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Perinatal Thrombosis in Mice Resulting From the Interaction of Tissue Factor Pathway Inhibitor Deficiency and Factor V Leiden

Abstract: Background — Factor V Leiden (FVL) is a common genetic risk factor for thrombosis in humans. The incomplete penetrance of FVL suggests important contributions from other genetic or environmental modifying factors. Variation in the expression of tissue factor pathway inhibitor ( TFPI ) has also been proposed as a risk factor for venous thrombosis and has been shown to enhance the prothrombotic effect of FVL in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 22 publications
(21 reference statements)
1
65
1
Order By: Relevance
“…162,163 Transgenic mice obtained by crossing mice with reduced levels of TFPI with mice homozygous for factor V LEIDEN resulted in mice with a lethal phenotype with fibrin deposition in multiple organs. 164 The observation of disseminated thrombosis in mice homozygous for the factor V LEIDEN mutation and low levels of TFPI is in keeping with the hypothesis suggested by in vitro data. 163 Thus, reduced TFPI levels may be a contributor to thrombosis in association with factor V LEIDEN .…”
Section: Potential Influence Of Combined Pathology Associated With Fasupporting
confidence: 83%
“…162,163 Transgenic mice obtained by crossing mice with reduced levels of TFPI with mice homozygous for factor V LEIDEN resulted in mice with a lethal phenotype with fibrin deposition in multiple organs. 164 The observation of disseminated thrombosis in mice homozygous for the factor V LEIDEN mutation and low levels of TFPI is in keeping with the hypothesis suggested by in vitro data. 163 Thus, reduced TFPI levels may be a contributor to thrombosis in association with factor V LEIDEN .…”
Section: Potential Influence Of Combined Pathology Associated With Fasupporting
confidence: 83%
“…Previous studies have demonstrated that Tfpi +/− contributes to a severe thrombosis in mice when in the presence of an underlying procoagulant state, such as the factor V Leiden mutation (26) or decreased thrombomodulin function (27). Conversely, studies performed here show that breeding of Tfpi +/− to F8 −/− mice does not alter the hemophilia bleeding phenotype, as assessed using whole-blood TEG and tail bleeding assays.…”
Section: Discussioncontrasting
confidence: 51%
“…44 TFPI from trophoblasts as well as from the maternal circulation in the TFPI Tie2 mice may be sufficient to maintain the TF-TFPI balance required for placental hemostasis and embryogenesis. When TFPI heterozygosity (TFPI ϩ/Ϫ ) is bred into mice with other prothrombotic genetic traits such as factor V Leiden 13 or thrombomodulin deficiency, 14 thrombotic disease occurs with multiple manifestations including intrauterine lethality, perinatal lethality, and hypercoagulability in surviving adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…11 Heterozygotic deletion results in an increased response to acute and chronic vascular injury. [12][13][14] Conversely, vasculardirected overexpression of TFPI attenuates this response. 15 To better define the cellular sources of TFPI and their role in development, hemostasis, and thrombosis, we generated mice with endothelial and monocytic-restricted deletion of exon 4, which encodes for the TFPI-K1 domain.…”
mentioning
confidence: 99%